Association between exposure to social media and knowledge of sexual and reproductive health among adolescent girls: evidence from the UDAYA survey in Bihar and Uttar Pradesh, India - Ria Saha; Pintu Paul; Sanni Yaya; Aduragbemi Banke-Thomas (BMC, 2022)
Plain language summary A substantial body of research shows that adolescent girls in India lack adequate sexual and reproductive health (SRH) knowledge. Evidently, this puts them at several health risks associated with early pregnancies, preventable gynecological morbidities such as irregular menstrual patterns, and urethral discharge, among several others. Perpetuated social stigma and lack of agency impede adolescents especially from marginalized communities from accessing accurate, sufficient, and timely SRH information from their immediate household members and healthcare providers at local service points. This adversely affects their health-seeking behaviors and ultimately results in avertable poor reproductive health outcomes. A growing body of literature highlights social media platforms (i.e., Facebook, Instagram, Twitter, etc.) as preferred modalities to gain SRH information among adolescents. Against this backdrop, we assessed the intricate association between social media exposure and SRH knowledge (across three dimensions: sexual intercourse and pregnancy, contraceptive methods, and HIV/AIDS) among adolescent girls in Bihar and Uttar Pradesh, India. We tested for association between several socio-demographic factors and SRH knowledge. Findings indicate that adolescents who were exposed to social media platforms were likely to have more SRH knowledge compared to those who were not. Socio-demographic factors like place of residence, for example residing in urban areas, higher levels of education and high wealth index acted as facilitators of social media exposure as well as SRH knowledge.